1996
DOI: 10.1111/j.2042-7174.1996.tb00867.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the community pharmacist in the care of patients with chronic schizophrenia in the community

Abstract: This study, using a postal questionnaire, investigated the involvement of 534 community pharmacists with patients suffering from schizophrenia. The majority of the 236 respondents regularly dispensed medication for patients with schizophrenia and almost three-quarters had been asked for advice about medication from such patients or their carers. However, the majority of respondents believed that the advice they could give to these patients was limited by their knowledge of schizophrenia (86 per cent) and of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 12 publications
3
32
1
Order By: Relevance
“…27,28 The use of consumers as educators has largely been restricted to nursing and medical education, where their contribution has been reported to be well received. 36 Other reported advantages of using consumers are improved attitudes and a positive impact on nursing practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 The use of consumers as educators has largely been restricted to nursing and medical education, where their contribution has been reported to be well received. 36 Other reported advantages of using consumers are improved attitudes and a positive impact on nursing practices.…”
Section: Discussionmentioning
confidence: 99%
“…27 British and Canadian community pharmacists have reported that their ability to provide information about antipsychotic medications is limited by a lack of training to counsel people with severe mental illnesses. 27,28 Dutch community pharmacists did not perceive that they have a clear role in the management of schizophrenia. 29 In the same study, however, 60% of people with schizophrenia and their caregivers indicated they would like to receive more information about prescribed medications.…”
Section: -25mentioning
confidence: 99%
“…However, mental health stigma and lack of knowledge of mental illness can interfere with their professional practice. 7,12 For example, pharmacists are more confident in providing pharmaceutical services for patients with a cardiovascular illness than for those with a mental illness. 12 Also, pharmacists have negative beliefs about depression similar to those held by the general population 13 and suboptimal attitudes towards mental illness are common among health care professionals in general.…”
Section: Introductionmentioning
confidence: 99%
“…14 Patients with mental illness are often dissatisfied with the quality and quantity of drug information provided to them. 7 The lack of mental health pharmacy education has been described as the main barrier to successful provision of pharmaceutical services for consumers with a mental illness. 15 The World Health Organization recognizes that good communication skills are essential for all health care workers engaged in mental health care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation